The Incidence of Intraventricular Hemorrhage in Low-Birth-Weight Infants: Assessment by Magnetic Resonance Imaging - Hayakawa, Katsumi; Tanda, Koichi; Nishimoto, Masakazu; Nishimura, Akira; Kinoshita, Daisuke; Sano, Yuko (Neuropediatrics, 2022)
Purpose Intraventricular hemorrhage (IVH) is common in infants with a low-birth-weight (LBW) and has been suggested to cause major impairment not only of future motor development but also of cognitive function and learning ability. The purpose of the present study is to assess the frequency of IVH using magnetic resonance imaging (MRI) in LBW infants and its clinical neurodevelopmental outcomes.Methods We enrolled a consecutive series of 247 neonates with an LBW of < 1,500 g hospitalized in the newborn intensive care unit between 2010 and 2015. The presence of IVH was examined using T2* MRI at term-equivalent age (TEA). We then investigated the clinical outcome at ≥3 years of age and its correlation with the IVH grade.Results The overall incidence of IVH among LBW infants was 16.2%. The proportion of infants with IVH showing a favorable outcome did not differ significantly from that of infants without IVH. The proportion of neonates showing a poor outcome was 6.7% for those with IVH and 1.9% for those without IVH and 2.7% for those with and without IVH combined.Conclusion We were able to clarify the frequency of IVH in LBW infants using MRI at TEA. We demonstrated the lower incidence of mortality and IVH, the higher incidence of a favorable outcome, and the lower incidence of poor outcome.
Keywords: magnetic resonance imaging; newborn; low-birth-weight infants; intraventricular hemorrhage